2023
DOI: 10.26776/ijemm.07.02.2023.02
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Modified Microwave-assisted Rapid Hydrothermal Liquefaction Process for Conversion of Palm Kernel Shells to Bio-oil

Abstract: Bio-oil is one of the potential resources to address the sustainable energy development and environmental issues. Microwave-assisted Rapid Hydrothermal Liquefaction Process is one of the popular techniques that is used to extract bio-oil from biomass. In this paper, the bio-oil has been extracted from Palm Kernel Shells by using microwave-assisted and conventional heating pyrolysis processes. A modified heating mantle apparatus are used to conduct the experiment for extracting the bio-oil. The experiments are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A study reported that calorific value of bio oil of Moringa Seed and Karanja are much lower than commercial fuel such as diesel with calorific value of 45.18 MJ/kg and heavy fuel oil with calorific value of 42.5 MJ/kg which indicated that bio oil content is higher in oxygenated compounds and condensed water (Hawash et al, 2017;Ravikumar et al, 2017). Bio oil of Karanja has lower heating value due to high moisture content of raw materials during microwave pyrolysis (Ibrahim et al, 2012;Saleh et al, 2023). A study reported that bio oil obtained from corn stover has a pH value of 2.87 and most of the bio oil have a pH range of 2.0 -3.8.…”
Section: Bio-oil Charecterizationmentioning
confidence: 99%
“…A study reported that calorific value of bio oil of Moringa Seed and Karanja are much lower than commercial fuel such as diesel with calorific value of 45.18 MJ/kg and heavy fuel oil with calorific value of 42.5 MJ/kg which indicated that bio oil content is higher in oxygenated compounds and condensed water (Hawash et al, 2017;Ravikumar et al, 2017). Bio oil of Karanja has lower heating value due to high moisture content of raw materials during microwave pyrolysis (Ibrahim et al, 2012;Saleh et al, 2023). A study reported that bio oil obtained from corn stover has a pH value of 2.87 and most of the bio oil have a pH range of 2.0 -3.8.…”
Section: Bio-oil Charecterizationmentioning
confidence: 99%